“Cid sons, in you it keeps the memory of this hero!” An approach to National Militia of Burgos (1833-1843) (History Journal «Jerónimo Zurita», 2023)
The National Militia was a key player in the period 1833-1843. In this present article proposes an analysis of the Militia of the city of Burgos: its social composition, its organisation, its clothing and weaponry, its political culture in terms of civic festivities and speeches, until its end and its political culture around civic festivities and speeches, until its end in the crisis of 1843.
Keywords: National Militia, Burgos, political culture, politicisation, liberalism